Clinical, biochemical and genetic characteristics of MOGS-CDG: a rare congenital disorder of glycosylation. Issue 11 (5th July 2022) - Shimada, Shino; Ng, Bobby G; White, Amy L; Nickander, Kim K; Turgeon, Coleman; Liedtke, Kristen L; Lam, Christina T; Font-Montgomery, Esperanza; Lourenco, Charles M; He, Miao; Peck, Dawn S; Umana, Luis A; et al.
Abstract : Purpose: To summarise the clinical, molecular and biochemical phenotype of mannosyl-oligosaccharide glucosidase-related congenital disorders of glycosylation (MOGS-CDG), which presents with variable clinical manifestations, and to analyse which clinical biochemical assay consistently supports diagnosis in individuals with bi-allelic variants in MOGS . Methods: Phenotypic characterisation was performed through an international and multicentre collaboration. Genetic testing was done by exome sequencing and targeted arrays. Biochemical assays on serum and urine were performed to delineate the biochemical signature of MOGS-CDG. Results: Clinical phenotyping revealed heterogeneity in MOGS-CDG, including neurological, immunological and skeletal phenotypes. Bi-allelic variants in MOGS were identified in 12 individuals from 11 families. The severity in each organ system was variable, without definite genotype correlation. Urine oligosaccharide analysis was consistently abnormal for all affected probands, whereas other biochemical analyses such as serum transferrin analysis was not consistently abnormal. Conclusion: The clinical phenotype of MOGS-CDG includes multisystemic involvement with variable severity. Molecular analysis, combined with biochemical testing, is important for diagnosis. In MOGS-CDG, urine oligosaccharide analysis via matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry can be used as a reliable biochemical test for screening and confirmation of disease.